PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP LOYALITAS PELANGGAN PADA CAFÉ FORE BANDAR LAMPUNG - Yuta Hijriyah Amanda; Iskandar Ali Alam (Jurnal Widya, 2023)
The goal of this study is to discover how customer loyalty at Café FORE Bandar Lampung is impacted by product pricing and quality. The population of the study consists of Café FORE Bandar Lampung customers, and the slovin formula predicts that the sample size is 100. using multiple linear regression analysis as an analysis technique. The study's conclusions, which have been shown to be true, indicate that customer loyalty at Café FORE Bandar Lampung is favorably and significantly influenced by both product quality and pricing. It is believed that with the aid of this research, Café FORE Bandar Lampung can uphold consistent product quality and affordable prices for customers, hence increasing customer loyalty.